1997
DOI: 10.1002/(sici)1097-0339(199703)16:3<214::aid-dc4>3.3.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐needle aspiration of subacute granulomatous thyroiditis (De Quervain's thyroiditis): A clinico‐cytologic review of 36 cases

Abstract: Although subacute granulomatous thyroiditis (SGT) is usually diagnosed clinically, there are other thyroid conditions that must be ruled out. This task is achieved by means of fine-needle aspiration (FNA). In retrospect, the clinical and cytologic findings seen in 36 SGT cases are reassessed with a view to deciding which findings are most reliable for reaching a confident cytologic diagnosis. These are: the simultaneous presence in the same aspirate of the following cells: 1) follicular cells with intravacuola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 7 publications
1
10
1
Order By: Relevance
“…FNA cytology is characterized by epithelioid granulomas, MNGCs, and an acute and chronic inflammatory ''dirty'' background. Solano et al 6 reported on the presence of follicular cells with intravacuolar granules and/or plump transformed follicular cells, a finding not appreciated in our cases. MNGCs seen in our cases of subacute thyroiditis tended to be the most numerous, the largest, and with the most number of nuclei.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…FNA cytology is characterized by epithelioid granulomas, MNGCs, and an acute and chronic inflammatory ''dirty'' background. Solano et al 6 reported on the presence of follicular cells with intravacuolar granules and/or plump transformed follicular cells, a finding not appreciated in our cases. MNGCs seen in our cases of subacute thyroiditis tended to be the most numerous, the largest, and with the most number of nuclei.…”
Section: Discussioncontrasting
confidence: 41%
“…They have also been reported in a broad spectrum of diseases ranging from palpation thyroiditis to drug reactions such as fenitoins, postsurgical reactions, postradionucleotide scan, follicular neoplasms, Hashimoto's thyroiditis, and others. [2][3][4][5][6][7][8] Osteoclast-like giant cells have been reported in rare cases of anaplastic carcinomas. 9,10 This study was undertaken to see whether the quantity and/or quality, i.e., the morphologic characteristics of MNGCs as seen on fine-needle aspiration (FNA) of thyroid nodules, can help in the differential diagnosis of these diagnostic possibilities.…”
mentioning
confidence: 99%
“…Multinucleated giant cells (MGCs) are reported to occur in both benign and malignant thyroid gland lesions, most commonly including papillary carcinoma, Hashimoto's thyroiditis and granulomatous thyroiditis . Their origin and presence in cases of PTC has been the subject of several studies dating to the 1980s.…”
Section: Discussionmentioning
confidence: 99%
“…The reactive follicular epithelium in chronic lymphocytic thyroiditis is usually adjacent to the inflammatory infiltrate and with focal nuclear atypia showing some but not all features of PTC [53,55]. Identifying the multinucleated giant cells, epithelioid histiocytes, and fibrotic stromal fragments in the complex background created by acute-chronic inflammation and debris can improve the sensitivity for the diagnosis of granulomatous thyroiditis [56][57][58]. However, it should be noted that the presence of multinucleated giant cells does not rule out the diagnosis of thyroid cancer.…”
Section: Analysis Of the False-positive Casesmentioning
confidence: 99%